Noir anxiety - Oliver, Kelly, 1958- (University of Minnesota Press, 2003)
In Noir Anxiety, Kelly Oliver and Benigno Trigo interpret what has been called the "free-floating anxiety" of film noir as concrete apprehensions about race and sexuality.